The Use of Scientific Paradigms In the Aid For The Resolution of Difficult Cases of Interdisciplinary Nature In Various Areas of Law (Revista Direito em Debate, 2022)
Technology and several technological developments have always interfered, it has been used directly or had subsidiary applicability in the way how mankind interpreted natural and social phenomena. It is clear by historical accounts that this interference influences in the various decisions about the so-called "controversial" or "difficult cases" subjects of the most diverse cultures and societies. The search for answers led the human being to propose explanations that are scientifically accepted, theoretically demonstrable, ascertainable, or reasonably assumed as valid, the so-called scientific paradigms. These paradigms also interfere and are applied in the law’s sphere and can be used to assist this area of knowledge in solving issues that are not tangible to their study. This way, the present work has a study of how the background in other areas of knowledge, including the Natural Sciences, help the Law in the resolution of divergences that are not addressed by its original methodological scope, but which become more and more present.
Keywords: Auxiliary sciences of Law, Conflict resolutions, Relationship between technological knowledge and legal knowledge